A water-retaining rare earth functional glaze for ceramics and its preparation method and application

Through the application of rare earthy glaze additives on the ceramic cup, the problem of water quality that cannot be effectively maintained by the ceramic cup can be solved, the high -efficiency water reservation performance of the ceramic cup is achieved, and the water quality standard for drinking water is met.

CN118637819BActive Publication Date: 2025-01-28TIANJIN BAOGANG RES INST OF RARE EARTHS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411110204.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-28
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

Existing ceramic cups cannot effectively maintain water quality when storing and drinking water, and the effluent pH value of reverse osmosis technology does not meet drinking water standards.

Method used

The preparation method of rare earth function glaze additives is used to form a carbon skeleton structure under the heating conditions of the iron source, carbon source, rare earth salt and titanium dioxide under heating conditions. Essence The additive improves the water retention quality of the ceramic cup by combining with ceramic glazed surface.

Benefits of technology

It significantly improves the solubility of the ceramic cup to water, enhances the water retention quality of the ceramic cup, and the soluble oxygen amount of the ceramic cup made is about 2.18 times, which meets the water quality standards of drinking water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637819B_ABST
    Figure CN118637819B_ABST
Patent Text Reader

Abstract

The present invention provides a water-retaining rare earth functional glaze for ceramics and a preparation method and application thereof, wherein the addition amount of the rare earth functional slurry in the glaze is 5-25%, the rare earth functional slurry is prepared from a rare earth functional glaze additive, water, and polyvinyl pyrrolidone, and the preparation method of the rare earth functional glaze additive comprises the following steps: S1: uniformly mixing an iron source, a carbon source, a first rare earth salt, and a second rare earth salt, adding alkali solution thereto, stirring under heating conditions, cooling to room temperature after the reaction is complete, and then adding titanium dioxide to obtain a mixture; S2: placing the mixture obtained in step S1 into the lining of an autoclave, and reacting in the autoclave, and obtaining an intermediate after the reaction is completed; S3: filtering, drying, and calcining the intermediate obtained in step S2 to obtain a rare earth functional glaze additive. The glaze of the present invention increases the amount of dissolved oxygen in water on a conventional ceramic glaze surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic glaze preparation, and in particular relates to a water-retaining rare earth functional glaze for ceramics, and a preparation method and application thereof. Background Art

[0002] Rare earth elements are a group of important chemical elements that play a vital role in modern technology and industry. Despite their name, they are not actually rare, but widely found in the earth's crust. With the combination of rare earth nanomaterials with dopants or active substances and other functional ligands, photodynamic therapy and bioimaging methods have been gradually enhanced.

[0003] With the development of economy and the vigorous promotion of industrialization, the purification of drinking water has become more and more important in our society. In recent years, reverse osmosis (RO) and nanofiltration (NF) technologies have been widely used in water treatment. Compared with reverse osmosis, nanofiltration requires lower working pressure and lower energy consumption. The pH value of RO effluent is 5.8-6, which does not meet the pH value requirement of 6.5-8.5 in the Drinking Water Quality Standard (GB5749-2006). Ceramic cups have become the most popular drinking water tea sets in China. The introduction of rare earth elements to ceramic cups is expected to improve the quality of drinking water. Summary of the invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a water-retaining rare earth functional glaze for ceramics and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] In a first aspect, the present invention provides a method for preparing a rare earth functional glaze additive, comprising the following steps:

[0007] S1: uniformly mixing an iron source, a carbon source, a first rare earth salt, and a second rare earth salt, adding an alkali solution thereto, stirring under heating conditions, cooling to room temperature after the reaction is complete, and then adding titanium dioxide to obtain a mixture;

[0008] S2: placing the mixture obtained in step S1 into the inner lining of a high-pressure reactor and reacting in the high-pressure reactor to obtain an intermediate after the reaction is completed;

[0009] S3: The intermediate obtained in step S2 is filtered, dried, and calcined to obtain a rare earth functional glaze additive.

[0010] Preferably, in step S1, the mass ratio of the iron source, the carbon source, the first rare earth salt, the second rare earth salt and titanium dioxide is (1-3): (5-15): (3-8): (3-8): (1-3).

[0011] Preferably, the alkali solution in step S1 is one or more of ammonia water, sodium bicarbonate aqueous solution, sodium carbonate aqueous solution, and ammonium carbonate aqueous solution, and the mass concentration of the alkali solution is 20-29%, and the solid-liquid ratio is (13-37): (15-30).

[0012] Preferably, the iron source is ferric chloride and / or ferric nitrate.

[0013] Preferably, the carbon source is one or more of cyanamide, melamine and dicyandiamide.

[0014] Preferably, the first rare earth salt and the second rare earth salt have the same anion.

[0015] Preferably, the first rare earth salt and the second rare earth salt are both selected from La(NO3)3·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O, Gd(NO3)3·6H2O, Sm(NO3)3·6H2O, LaCl3·7H2O, CeCl3·6H2O, YCl3·6H2O, GdCl3·6H2O, SmCl3·6H2O, La2(SO4)3·8H2O, Ce2(SO4)3·4H2O, Gd2(SO4)3·8H2O, Sm2(SO4)3·8H2O, La2(C2O4)3·10H2O, Ce2(C2O4)3, Gd2(C2O4)3·10H2O, Sm2(C2O4)3·10H2O.

[0016] Preferably, the temperature of the heating step in step S1 is 70-100° C., and the stirring time is 2-4 hours.

[0017] Preferably, the inner lining of the high-pressure reactor in step S2 is made of polytetrafluoroethylene.

[0018] Preferably, the reaction temperature in step S2 is 150-200° C. and the reaction time is 1-4 hours.

[0019] Preferably, the filtration step in step S3 uses medium-speed filter paper and the filtration temperature is 20-30°C.

[0020] Preferably, the calcination step in step S3 is carried out at a temperature of 500-700° C., for a time of 2-5 hours, and at a heating rate of 5-10° C. / min.

[0021] In a second aspect, the present invention also provides a rare earth functional slurry prepared by using the above rare earth functional glaze additive.

[0022] Preferably, the rare earth functional slurry is prepared from rare earth functional glaze additive, water and polyvinyl pyrrolidone, wherein the mass ratio of the rare earth functional glaze additive, water and polyvinyl pyrrolidone is (1-3): (2-5): (0.01-0.05).

[0023] In a third aspect, the present invention also provides a water-retaining rare earth functional glaze for ceramics prepared by applying the above rare earth functional slurry, wherein the amount of the slurry added to the glaze is 5-25%.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) The rare earth functional glaze additive of the present invention is synthesized from iron source, carbon source, titanium dioxide and rare earth salt as raw materials. After alkalization, the carbon skeleton formed by high-temperature polycondensation of ferric chloride and cyanamide has many active sites, which can form stable coordination bonds with rare earth ions, promote the rare earth ions and carbon materials, iron elements, and titanium dioxide to jointly improve the water retention performance of ceramic cups.

[0026] (2) The rare earth functional glaze additive of the present invention increases the dissolved oxygen content of conventional ceramic glazes in water after loading rare earth on the surface of the carbon skeleton. The dissolved oxygen content of the ceramic cup prepared by LGCO is increased by about 2.18 times compared with the blank. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the LGCO prepared in Example 1 of the present invention;

[0028] Figure 2 This is a bar graph of dissolved oxygen test of some ceramic cups prepared in Example 7 of the present invention;

[0029] Figure 3 This is a bar graph of dissolved oxygen test of the nitric acid series ceramic cup prepared in Example 7 of the present invention;

[0030] Figure 4 This is a bar graph of the dissolved oxygen test of the sulfuric acid series ceramic cup prepared in Example 7 of the present invention;

[0031] Figure 5 This is a bar graph of dissolved oxygen test of the chloride series ceramic cup prepared in Example 7 of the present invention;

[0032] Figure 6 This is a bar graph of dissolved oxygen test of a ceramic cup prepared by LCCO, LCNO, LCSO and LCCL described in Example 1 of the present invention;

[0033] Figure 7This is a bar graph showing the dissolved oxygen test of the ceramic cup prepared by LGCO in Example 7 of the present invention and the ceramic cups prepared by Comparative Examples 2 and 3;

[0034] Figure 8 A bar graph showing the dissolved oxygen content of the ceramic cup prepared from LGCO in Example 7 of the present invention and the ceramic cups prepared from Comparative Examples 4 and 5. DETAILED DESCRIPTION

[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0036] The present invention will be described in detail below with reference to the embodiments.

[0037] The sources of materials used in the embodiments and comparative examples are:

[0038] Ferric chloride, cyanamide, ferric nitrate, melamine, dicyandiamide, titanium dioxide, and ammonia (NH ·H O) were purchased from Beijing Solebow Technology Co., Ltd.;

[0039] La(NO3)3·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O, Gd(NO3)3·6H2O, Sm(NO3)3·6H2O, LaCl3·7H2O, CeCl3·6H2O, YCl3·6H2O, GdCl3·6H2O, SmCl3·6H2O, La2(SO4)3·8H2O, Ce2(SO4)3·4H2O, Gd2(SO4)3·8H2O, Sm2(SO4)3·8H2O, La2(C2O4)3·10H2O, Ce2(C2O4)3, Gd2(C2O4)3·10H2O, Sm2(C2O4)3·10H2O were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. All chemicals were used without further treatment;

[0040] Distilled water (ρ = 18.2 MΩ•cm, 25°C) was from a Millipore milli-Q water purification system;

[0041] Prepare manganese sulfate solution: add 36g manganese sulfate tetrahydrate into a 1L volumetric flask, make up to 1L, and shake well to dissolve;

[0042] Prepare alkaline potassium iodide solution: dissolve 500g sodium hydroxide in 300mL water, dissolve 150g potassium iodide in 200mL water, mix the potassium iodide and sodium hydroxide solutions and add to a 1L volumetric flask, dilute to 1L, and shake well;

[0043] Prepare sodium thiosulfate solution: add 6.2g of sodium thiosulfate pentahydrate to 1L of boiling water, make sure there is no oxygen inside, and then add 0.2g of sodium carbonate.

[0044] The present invention will be described in detail below with reference to the embodiments.

[0045] Example 1

[0046] A method for preparing a rare earth functional glaze additive comprises the following steps:

[0047] Dissolve 1g of ferric chloride in 300mL of pure water, then add 10g of cyanamide and stir evenly. Then add 5g of lanthanum oxalate decahydrate and 5g of gadolinium oxalate decahydrate and stir to dissolve. Then, add 15mL of 28% ammonia water with a separatory funnel and stir at 80°C for 3 hours. After the reaction is cooled to room temperature, add 1g of titanium dioxide powder.

[0048] The mixture was placed in a polytetrafluoroethylene liner and then in an autoclave, reacted at 160°C for 2 hours to obtain an intermediate, the intermediate was filtered, and the filter residue was dried to obtain a dry intermediate powder, and then the intermediate powder was added to a crucible, placed in a muffle furnace, and calcined at 650°C for 3 hours at a heating rate of 5°C / min to prepare a rare earth functional glaze additive. The material synthesized according to this method is named LGCO, and its scanning electron microscope image is as follows Figure 1 As shown, it can be seen that the carbon skeleton is formed by the high-temperature polycondensation of ferric chloride and cyanamide. The nanoclusters in the scanning electron microscope are attached to the two-dimensional layered structure, which proves that the carbon skeleton can be formed by the high-temperature polymerization of cyanamide, and the double rare earth exists stably in the form of oxide nanoclusters above the carbon skeleton. It can be observed from the figure that the bottom two-dimensional structure has many pores. This is because the formation of the carbon skeleton brings many vacancies to the structure. These vacancies make the material have a larger specific surface area, thereby increasing the active sites of the material itself and enhancing the performance of the material.

[0049] The oxalate anion series samples were prepared according to the same experimental steps:

[0050] LCCO, LSCO, CGCO, CSCO, GSCO;

[0051] A series of nitrate anion samples were prepared according to the same experimental steps:

[0052] LCNO, LGNO, LSNO, CGNO, CSNO, GSNO;

[0053] Chloride anion series samples were prepared according to the same experimental steps:

[0054] LCCL, LGCL, LSCL, CGCL, CSCL, GSCL;

[0055] The sulfate anion series samples were prepared according to the same experimental steps:

[0056] LCSO, LGSO, LSSO, CGSO, CSSO, GSSO;

[0057] In addition, samples of single rare earth salts (i.e., the amount of rare earth salt added was 10 g) were prepared according to the same experimental procedures: LCO, CNO, SCL, and GSO.

[0058] In the above samples: lanthanum is abbreviated as L; cerium is abbreviated as C; gadolinium is abbreviated as G; and samarium is abbreviated as S.

[0059] Example 2

[0060] Dissolve 3g of ferric nitrate in 300mL of pure water, then add 5g of melamine and stir evenly. Then add 3g of lanthanum oxalate decahydrate and 3g of gadolinium oxalate decahydrate and stir to dissolve. Use a separatory funnel to drop 15mL of 20% sodium bicarbonate aqueous solution, then stir at 80°C for 3 hours. After the reaction is cooled to room temperature, add 2g of titanium dioxide powder.

[0061] The mixture was placed in a polytetrafluoroethylene liner and then in an autoclave, reacted at 160°C for 2 hours to obtain an intermediate, the intermediate was filtered, and the filter residue was dried to obtain a dry intermediate powder, and then the intermediate powder was added to a crucible, placed in a muffle furnace, calcined at 650°C for 3 hours, and the heating rate was 5°C / min to prepare a rare earth functional glaze additive.

[0062] Example 3

[0063] Dissolve 2g of ferric chloride in 300mL of pure water, then add 15g of dicyandiamide and stir evenly. Add 8g of lanthanum oxalate decahydrate and 8g of gadolinium oxalate decahydrate and stir to dissolve. Use a separatory funnel to drop 30mL of 29% sodium carbonate aqueous solution, then stir at 80°C for 3 hours. After the reaction is cooled to room temperature, add 3g of titanium dioxide powder.

[0064] The mixture was placed in a polytetrafluoroethylene liner and then in an autoclave, reacted at 160°C for 2 hours to obtain an intermediate, the intermediate was filtered, and the filter residue was dried to obtain a dry intermediate powder, and then the intermediate powder was added to a crucible, placed in a muffle furnace, calcined at 650°C for 3 hours, and the heating rate was 5°C / min to prepare a rare earth functional glaze additive.

[0065] Example 4

[0066] The preparation of rare earth functional slurry comprises the following steps:

[0067] Take 250g of the powder material prepared in Example 1, add 750mL of pure water and 10g of polyvinyl pyrrolidone respectively, stir evenly, and then use a sand mill for sand grinding. The sand mill cavity is filled with 80% zirconium dioxide sand mill beads, the radius of the grinding beads is 0.5mm, and the sand mill speed is adjusted to 3200rpm. The temperature of the sand mill outlet and the sand mill cavity is controlled at 25°C, and the sand mill time is 5 hours.

[0068] Example 5

[0069] The preparation of rare earth functional slurry comprises the following steps:

[0070] Take 250g of the powder material prepared in Example 1, add 1250mL of pure water and 2.5g of polyvinyl pyrrolidone respectively, stir evenly, and then use a sand mill for sand grinding. The sand mill cavity is filled with 80% zirconium dioxide sand mill beads, the radius of the grinding beads is 0.5mm, and the sand mill speed is adjusted to 3200rpm. The temperature of the sand mill outlet and the sand mill cavity is controlled at 25°C, and the sand mill time is 5 hours.

[0071] Example 6

[0072] The preparation of rare earth functional slurry comprises the following steps:

[0073] Take 450g of the powder material prepared in Example 1, add 300mL of pure water and 7.5g of polyvinyl pyrrolidone respectively, stir evenly, and then use a sand mill for sand grinding. The sand mill cavity is filled with 80% zirconium dioxide sand mill beads, the radius of the grinding beads is 0.5mm, and the sand mill speed is adjusted to 3200rpm. The temperature of the sand mill outlet and the sand mill cavity is controlled at 25°C, and the sand mill time is 5 hours.

[0074] Example 7

[0075] The preparation of a water-retaining ceramic cup containing a rare earth functional glaze additive comprises the following steps:

[0076] Take quartz, feldspar and porcelain clay with a mass percentage of 40% and add them to a pulverizer to crush large particles into small pieces. The crushed small pieces are added to a ball mill and further ground to make the final particle size of the mixed powder approximately less than 10 microns. 10% of the rare earth functional slurry prepared in Example 4 is added to the ball mill, and the ball milling is continued to make the particle size finally controlled to be about 2 microns, and then an appropriate amount of water is added for dispersion, and the glaze is evenly sprayed on the surface of the ceramic blank using a handheld sprayer, and finally calcined at 1000°C for 12 hours to obtain a water-retaining ceramic cup containing a rare earth functional glaze additive.

[0077] Example 8

[0078] The preparation of a water-retaining ceramic cup containing a rare earth functional glaze additive comprises the following steps:

[0079] Take quartz, feldspar and porcelain clay with a mass percentage of 40% and add them to a pulverizer to crush large particles into small pieces. The crushed small pieces are added to a ball mill and further ground to make the final particle size of the mixed powder approximately below 10 microns. Add 5% of the rare earth functional slurry prepared in Example 4 to the ball mill, continue ball milling, and finally control the particle size to about 2 microns. Then add an appropriate amount of water for dispersion, use a handheld sprayer to evenly spray the glaze on the surface of the ceramic blank, and finally calcine at 1000°C for 12 hours to obtain a water-retaining ceramic cup containing a rare earth functional glaze additive.

[0080] Example 9

[0081] The preparation of a water-retaining ceramic cup containing a rare earth functional glaze additive comprises the following steps:

[0082] Take quartz, feldspar and porcelain clay with a mass percentage of 40% and add them to a pulverizer to crush large particles into small pieces. The crushed small pieces are added to a ball mill and further ground to make the final particle size of the mixed powder approximately less than 10 microns. Add 25% of the rare earth functional slurry prepared in Example 4 to the ball mill, continue ball milling, and finally control the particle size to about 2 microns. Then add an appropriate amount of water for dispersion, use a handheld sprayer to evenly spray the glaze on the surface of the ceramic blank, and finally calcine at 1000°C for 12 hours to obtain a water-retaining ceramic cup containing a rare earth functional glaze additive.

[0083] Comparative Example 1

[0084] The difference between the ceramic cup of this comparative example and Example 7 is that no rare earth functional slurry is added, and a blank control ceramic cup without additives is prepared.

[0085] Comparative Example 2

[0086] The difference between the ceramic cup of this comparative example and Example 7 is that the rare earth functional glaze additive is only LGCO, and the added amount of the rare earth functional slurry is 4%.

[0087] Comparative Example 3

[0088] The difference between the ceramic cup of this comparative example and Example 7 is that the rare earth functional glaze additive is only LGCO, and the added amount of the rare earth functional slurry is 26%.

[0089] Comparative Example 4

[0090] The difference between the ceramic cup of this comparative example and Example 7 is that the amount of each component added during the preparation of the rare earth functional glaze additive in the rare earth functional slurry is: 1000g of rare earth functional glaze additive (LGCO), 750mL of water, and 10g of polyvinyl pyrrolidone. The preparation method of the rare earth functional glaze additive is the same as that of Example 1.

[0091] Comparative Example 5

[0092] The difference between the ceramic cup of this comparative example and Example 7 is that the amount of each component added during the preparation of the rare earth functional glaze additive in the rare earth functional slurry is: 125g of rare earth functional glaze additive (LGCO), 750mL of water, and 10g of polyvinyl pyrrolidone. The preparation method of the rare earth functional glaze additive is the same as that in Example 1.

[0093] Test Example: Dissolved Oxygen Test of Water

[0094] The dissolved oxygen content of water in various ceramic cups was tested. The test included the following steps:

[0095] Slowly add drinking water to the ceramic cup to be tested, fill the ceramic cup and overflow half, and ensure that there is no oxygen in the ceramic cup. Use a dropper to reach into the bottom of the manganese sulfate solution, suck back and forth twice to remove air, suck 1mL of manganese sulfate solution, and reach into the bottom of the drinking water in the ceramic cup to be tested, add manganese sulfate solution, and then continue to add 2mL of alkaline potassium iodide solution in the same way. After the precipitate is completely settled, continue to add 2mL of concentrated sulfuric acid (98%) in the same way. After the precipitate disappears, suck 100mL of the upper clear liquid and titrate with sodium thiosulfate solution. After the solution turns light yellow, add 1% starch solution, and then continue to titrate the sodium thiosulfate solution. When the solution just changes from blue to colorless, stop titrating and record the volume of sodium thiosulfate used.

[0096] The test results of dissolved oxygen in water of various ceramic cups are as follows: Figure 2-Figure 6 From the figure, it can be clearly seen that the functional glaze doped with two rare earth elements has a higher dissolved oxygen content than the functional glaze with a single rare earth element or without a rare earth element. Among them, LGCO has the highest dissolved oxygen content. This is mainly due to the fact that oxalate ions will corrode the carbon source under high temperature conditions to form products of thermal polycondensation, resulting in partial defects in the final framework formation and the existence of some defective structures, which provides a larger specific surface area for the material and increases the area in contact with water, thereby accelerating the redox reaction between rare earth ions and water molecules and increasing the oxygen content in the water. In addition, from Figure 7 and Figure 8 It can be seen that the addition ratio of rare earth functional slurry in the glaze and the additive ratio of rare earth functional glaze additives in the slurry will affect the dissolved oxygen content of the final product.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a rare earth functional glaze additive, characterized in that: The steps include: S1: uniformly mixing an iron source, a carbon source, a first rare earth salt, and a second rare earth salt, adding an alkali solution thereto, stirring under heating conditions, cooling to room temperature after the reaction is complete, and then adding titanium dioxide to obtain a mixture; S2: placing the mixture obtained in step S1 into the inner lining of a high-pressure reactor and reacting in the high-pressure reactor to obtain an intermediate after the reaction is completed; S3: filtering, drying, and calcining the intermediate obtained in step S2 to obtain a rare earth functional glaze additive; The iron source is ferric chloride and / or ferric nitrate; the carbon source is one or more of cyanamide, melamine, and dicyandiamide; the first rare earth salt and the second rare earth salt are both selected from La(NO3)3·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O, Gd(NO3)3·6H2O, Sm(NO3)3·6H2O, LaCl3·7H2O, CeCl3·6H2O, YC l3·6H2O, GdCl3·6H2O, SmCl3·6H2O, La2(SO4)3·8H2O, Ce2(SO4)3·4H2O, Gd2(SO4)3·8H2O, S m2(SO4)3·8H2O, La2(C2O4)3·10H2O, Ce2(C2O4)3, Gd2(C2O4)3·10H2O, Sm2(C2O4)3·10H2O; In step S1, the mass ratio of the iron source, the carbon source, the first rare earth salt, the second rare earth salt and titanium dioxide is (1-3): (5-15): (3-8): (3-8): (1-3); the temperature of the heating step in step S1 is 70-100°C, and the stirring time is 2-4 hours; the temperature of the reaction in step S2 is 150-200°C, and the time is 1-4 hours; the temperature of the calcination step in step S3 is 500-700°C, the time is 2-5 hours, and the heating rate is 5-10°C / min.

2. The preparation method according to claim 1, characterized in that: The alkali solution in step S1 is one or more of ammonia water, sodium bicarbonate aqueous solution, sodium carbonate aqueous solution, and ammonium carbonate aqueous solution. The mass concentration of the alkali solution is 20-29%, and the solid-liquid ratio is (13-37): (15-30).

3. The preparation method according to claim 1, characterized in that: The first rare earth salt and the second rare earth salt have the same anion.

4. The rare earth functional slurry prepared by using the rare earth functional glaze additive according to any one of claims 1 to 3 is characterized in that: The rare earth functional slurry is prepared from rare earth functional glaze additive, water and polyvinyl pyrrolidone, wherein the mass ratio of the rare earth functional glaze additive, water and polyvinyl pyrrolidone is (1-3): (2-5): (0.01-0.05).

5. A water-retaining rare earth functional glaze for ceramics prepared by using the rare earth functional slurry according to claim 4, wherein the addition amount of the rare earth functional slurry in the glaze is 5-25%.

Citation Information

Patent Citations

  • Composite rare earth modified zirconia ceramic powder and preparation method thereof

    CN109704759A

  • Rare-earth element adsorbent and preparation method and application thereof

    CN112717886A